Lithium lanthanum zirconium oxide solid electrolyte coated graphite lithium ion battery negative electrode material and preparation method thereof
Dopamine promotes uniform coating of lithium lanthanum zirconium oxygen solid electrolyte on the surface of natural graphite, solving the problems of large lithium ion diffusion resistance and poor electrolyte compatibility in lithium ion batteries, and improving the circulation stability and magnification of the material Performance, achieving high capacity and long cycle life of lithium-ion battery negative electrode material.
Patent Information
- Application Number
- CN202411429043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Natural graphite negative electrode materials have large lithium ion diffusion resistance, many surface defects, poor electrolyte compatibility, and lithium extraction phenomenon during high-speed charging, which cannot meet the needs of high-performance lithium ion batteries.
Dopamine is used to promote the uniform coating of lithium lanthanum zirconium oxygen solid electrolyte on the surface of natural graphite. It is stirred with natural graphite through dopamine hydrochloride dissolution, adjust the pH value, filter and vacuum drying, and then with lithium nitrate, lanthanum nitrate hexahydrate and oxychlorination of octahydrate Zirconium is mixed and heat treatment is carried out at high temperature to form a lithium lanthanum zirconium oxygen solid electrolyte coated graphite negative electrode material.
The capacity and cycle stability of natural graphite are improved, and the rate performance is enhanced. The specific capacity of the material reaches more than 340mAh/g. The circulation capacity of 450 weeks at 1C is basically unchanged, which solves the problem of not significantly improving the cycle life in the existing modification technology and The problem of negative impact on rate performance.
Smart Images

Figure CN119297240A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion battery negative electrode material of lithium lanthanum zirconium oxygen solid electrolyte coated with graphite and a preparation method thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] Lithium-ion secondary batteries, due to their green and environmentally friendly nature, high energy density, and reusability, can provide a feasible strategy for energy security and efficient and sustainable operation of new energy, and have extremely high application and research value.
[0003] In lithium-ion battery systems, graphite-based negative electrode materials have been used to this day and are currently the most widely used negative electrode materials. Graphite negative electrodes have the advantages of high capacity density, low potential, good conductivity, and abundant resources. They will be the first choice of negative electrode materials for lithium-ion batteries for a long time in the future.
[0004] Natural graphite is widely available and inexpensive, and is an important material for the negative electrode of lithium-ion batteries. However, natural graphite negative electrode materials still have the following disadvantages: (1) Natural graphite is anisotropic, which is not conducive to the diffusion of lithium ions. (2) There are many surface defects and poor compatibility with the electrolyte. (3) Cracks will form between the sheets due to the insertion and extraction of lithium ions, thereby increasing the Li + Diffusion resistance. (4) The lower electrode potential causes lithium deposition at the negative electrode when charged at a high rate. At present, the traditional graphite negative electrode can no longer meet the demand for high-performance lithium-ion batteries in social development. Therefore, many researchers have been committed to natural graphite modification technology. The main modification technologies include coating modification, surface treatment, element doping, etc.
[0005] Coating modification is a simple and effective modification method. Coating metal and its oxide materials on the surface of natural graphite can improve the cycle stability and rate performance of graphite negative electrode. Lithium lanthanum zirconium oxide solid electrolyte has excellent ionic conductivity and electrochemical stability, and is expected to improve the performance of natural graphite. However, the conventional method of coating lithium lanthanum zirconium oxide solid electrolyte on the surface of natural graphite has segregation problems and cannot achieve the expected effect. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a lithium ion battery negative electrode material of lithium lanthanum zirconium oxide solid electrolyte coated graphite and a preparation method thereof. Dopamine is used to promote the uniform coating of lithium lanthanum zirconium oxide solid electrolyte on the surface of natural graphite, which helps to improve the capacity and cycle stability of natural graphite.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for preparing a negative electrode material for a lithium-ion battery with a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite, the method comprising the following steps:
[0009] (1) dissolving dopamine hydrochloride in a mixed solution of water and ethanol, and then adding natural graphite and stirring to disperse uniformly to obtain a dispersion;
[0010] (2) adjusting the dispersion to be weakly alkaline, stirring to polymerize and adsorb dopamine on the surface of natural graphite, filtering, collecting powder and vacuum drying to obtain dopamine-coated graphite;
[0011] (3) dispersing the dopamine-coated graphite in deionized water, adding lithium nitrate, lanthanum nitrate hexahydrate and zirconium oxychloride octahydrate, and then adding citric acid monohydrate to obtain a mixed reaction system;
[0012] (4) heating and stirring until the solution in the mixed reaction system is evaporated to dryness, and vacuum drying the evaporated material to obtain a precursor material;
[0013] (5) The precursor material is transferred to a tubular furnace and subjected to heat treatment under a protective gas atmosphere to obtain a lithium ion battery negative electrode material having a lithium lanthanum zirconium oxide solid electrolyte coated with graphite.
[0014] Preferably, in step (1), the mass ratio of dopamine hydrochloride to natural graphite is 0.02 to 0.04:1.
[0015] Preferably, in step (1), the volume ratio of water to ethanol is 1:1 to 1.5.
[0016] Preferably, in step (2), NH3·H2O is added dropwise to adjust the pH value of the dispersion to 8.3-8.5.
[0017] Preferably, in step (2), the stirring rate is 200 to 300 rpm and the time is 24 to 32 hours.
[0018] Preferably, in step (2), deionized water and anhydrous ethanol are used alternately for filtration and washing until neutrality occurs.
[0019] Preferably, in step (2), the vacuum drying temperature is 60 to 80° C. and the time is 6 to 10 hours.
[0020] Preferably, in step (3), lithium nitrate, lanthanum nitrate hexahydrate, and zirconium oxychloride octahydrate are prepared in the following manner: 12 ) is added in a chemical dosage ratio, and an additional 10% to 12% excess lithium nitrate is added, and the corresponding lithium lanthanum zirconium oxygen mass is 3% to 10% of the mass of natural graphite. A certain amount of lithium nitrate is added to compensate for the lithium loss in the subsequent heating process.
[0021] Preferably, in step (3), the molar amount of citric acid monohydrate is 1.5 to 2 times that of the cation in the mixed reaction system.
[0022] Preferably, in step (4), the heating and stirring temperature is 70 to 90° C., and the stirring rate is 200 to 300 rpm.
[0023] Preferably, in step (4), the vacuum drying temperature is 60 to 80° C. and the time is 6 to 10 hours.
[0024] Preferably, in step (5), the protective gas is nitrogen or an inert gas (a gas element corresponding to all Group 0 elements on the periodic table).
[0025] Preferably, in step (5), the heat treatment temperature is 850-950°C, the treatment time is 5-7h, and the heating rate is 5-10°C / min.
[0026] A lithium-ion battery negative electrode material with lithium lanthanum zirconium oxygen solid electrolyte coated with graphite is prepared by the above method.
[0027] A lithium-ion battery, wherein the negative electrode material of the battery is a lithium-ion battery negative electrode material of lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as described in the present invention.
[0028] Beneficial Effects
[0029] The present invention dissolves dopamine hydrochloride in a mixed solution of water and ethanol, and then adds natural graphite to react to generate dopamine-coated graphite; then lithium nitrate, lanthanum nitrate hexahydrate, zirconium oxychloride octahydrate and dopamine-coated graphite are mixed according to a certain method, and then subjected to high-temperature heat treatment to obtain a lithium ion battery negative electrode material of lithium lanthanum zirconium oxygen solid electrolyte coated graphite. The method uses dopamine to pre-coat natural graphite, and utilizes the amphiphilic property of dopamine to make lithium lanthanum zirconium oxygen solid electrolyte uniformly coated on the surface of natural graphite without segregation, thereby ensuring the rate performance of the material while greatly improving the cycle performance of the material, and solving the shortcomings of the existing modification technology, such as the cycle life improvement is not obvious and the negative impact on the rate performance. The specific capacity of the negative electrode material prepared by the method of the present invention is more than 340mAh / g, and the cycle capacity of 450 weeks is basically unchanged at 1C. The dosage ratio of dopamine, lithium lanthanum zirconium oxygen and natural graphite in the preparation process, and the temperature and time in the heat treatment process can affect the structure and performance of the negative electrode material.
[0030] The method of the invention has the advantages of simple and safe preparation process, low cost, good continuity and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the SEM image of the final product in Example 1.
[0032] Figure 2 This is the EDS diagram of the final product in Example 1.
[0033] Figure 3-4 This is the XRD pattern of the final product in Example 1.
[0034] Figure 5 The cyclic performance diagram of the final product in Example 1 and Comparative Example 1.
[0035] Figure 6 The first week charge and discharge curves of the final products in Example 1 and Comparative Example 1 are shown.
[0036] Figure 7 This is the cycle performance diagram of the final product in Example 2.
[0037] Figure 8 This is the SEM image of the final product in Comparative Example 2.
[0038] Fig. 9 This is the cycle performance diagram of the final product in comparison 2.
[0039] Fig.10 This is the XRD diagram of the final product in Comparative Example 2.
[0040] Fig.11 This is the cycle performance diagram of the final product in Comparative Example 3. DETAILED DESCRIPTION
[0041] The present invention will be further described in detail below in conjunction with specific embodiments.
[0042] In the following examples and comparative examples:
[0043] Battery assembly and testing. The final product in the embodiment: Super P: sodium polyacrylate mixed in a mass ratio of 8:1:1 was coated on copper foil to make a negative electrode sheet, with a metal lithium sheet as the positive electrode, Ceglard2500 as the separator, and lb315 as the electrolyte. The battery was then left to stand for 8 hours and then cycled at a 1C rate, with a test voltage range of 0.005V-1.5V, and a 1C current density of 300mA / g.
[0044] Example 1
[0045] (1) 0.1 g of dopamine hydrochloride was dissolved in a mixed solution of water and ethanol in a volume ratio of 1:1, and then 5 g of natural graphite was added and stirred evenly.
[0046] (2) NH3·H2O was added dropwise to the above solution to adjust the pH value to 8.3, and the mixed solution was magnetically stirred at 200 rpm for 24 h to polymerize dopamine. The reaction solution was filtered, and washed with deionized water and anhydrous ethanol alternately until neutral, and the powder was collected and placed in an oven at 70°C for vacuum drying for 10 h to obtain dopamine-coated graphite.
[0047] (3) The dopamine-coated graphite is dispersed in deionized water, and lithium nitrate, lanthanum nitrate hexahydrate, and zirconium oxychloride octahydrate are added to the water in a stoichiometric ratio, with the corresponding mass of lithium lanthanum zirconium oxygen being 10% of that of natural graphite. Then, an additional 10% of lithium nitrate is added, and then citric acid monohydrate is added in a molar amount of 2 times the cationic amount.
[0048] (4) The mixed solution was magnetically stirred at 80°C at 300 rpm until the solution was evaporated to dryness, and then the evaporated material was placed in an oven at 80°C for vacuum drying for 10 h.
[0049] (5) The dried mixed material is transferred to a tubular furnace, and heated to 900° C. at a heating rate of 5° C. / min under argon gas protection for heat treatment for 7 h to obtain lithium lanthanum zirconium oxygen solid electrolyte coated graphite.
[0050] The SEM test results of the final product are as follows: Figure 1 As shown, the results indicate that the morphology of the natural graphite material after co-coating with the lithium lanthanum zirconium oxygen solid electrolyte has not changed significantly, and the original spherical graphite morphology characteristics are retained.
[0051] The EDS test results of the final product are as follows: Figure 2 As shown, the results show that the lithium lanthanum zirconium oxygen solid electrolyte is evenly distributed on the graphite surface, indicating that the lithium lanthanum zirconium oxygen solid electrolyte successfully coats natural graphite.
[0052] The XRD test results of the final product are as follows: Figure 3-4 As shown, the results show that the XRD diffraction pattern of natural graphite is not significantly changed after heat treatment.
[0053] The electrochemical performance test results of the final product are as follows Figure 5 , 6 As shown, the results show that the final product has a first-week charging capacity of 342.6 mAh / g and a first-week coulombic efficiency of 67.0%; in terms of cycle performance, the final product has a capacity of 339.9 mAh / g after 450 cycles at a current density of 1C, and a capacity retention rate of 99.4%.
[0054] Example 2
[0055] In step (2), the corresponding mass of lithium lanthanum zirconium oxide is 3% of natural graphite, and the rest is the same as in Example 1.
[0056] The SEM, EDS and XRD test results of the final product are similar to those in Example 1.
[0057] The electrochemical performance test results of the final product are as follows Figure 7 As shown, 3% lithium lanthanum zirconium oxygen solid electrolyte coated graphite was cycled for 700 weeks at a 1C rate, and the capacity remained at 290 mAh / g.
[0058] Comparative Example 1
[0059] The same battery assembly and testing was performed using natural graphite.
[0060] The electrochemical performance test results of the final product are as follows Figure 5 , 6 As shown, the results show that the final product has a first-week charging capacity of 350.7 mAh / g and a first-week coulombic efficiency of 65%; in terms of cycle performance, the final product has a capacity of 111.5 mAh / g after 450 cycles at a current density of 1C, and a capacity retention rate of 31.8%.
[0061] Comparative Example 2
[0062] Without using dopamine, natural graphite is directly coated with lithium lanthanum zirconium oxygen solid electrolyte.
[0063] (1) 5 g of natural graphite is dispersed in deionized water, and lithium nitrate, lanthanum nitrate hexahydrate, and zirconium oxychloride octahydrate are added to the water in a stoichiometric ratio, with the corresponding mass of lithium lanthanum zirconium oxygen being 10% of the added natural graphite. Then, an additional 10% of lithium nitrate is added, and then citric acid monohydrate is added in a molar amount of 2 times the cationic amount.
[0064] (2) The mixed solution was magnetically stirred at 80°C at 300 rpm until the solution was evaporated to dryness, and then the evaporated material was placed in an oven at 80°C for vacuum drying for 10 h.
[0065] (3) The dried mixed material was transferred to a tubular furnace, heated to 900° C. at a heating rate of 5° C. / min under argon gas protection, and heat treated for 7 h to obtain lithium lanthanum zirconium oxygen solid electrolyte coated graphite.
[0066] The SEM test results of the final product are as follows: Figure 8 As shown, the results indicate that segregated particles exist on the surface of natural graphite material after direct co-coating with lithium lanthanum zirconium oxygen solid electrolyte, and the natural graphite cannot be uniformly coated.
[0067] The electrochemical performance test results of the final product are as follows Fig. 9 As shown, the results show that the final product has a first-week charging capacity of 378.9 mAh / g and a first-week coulombic efficiency of 66.8%; in terms of cycle performance, the capacity of the final product decays rapidly at a current density of 1C and cannot work normally.
[0068] The EDS test results of the final product are as follows: Fig.10 As shown, the results indicate that the lithium lanthanum zirconium oxygen solid electrolyte obtained without the use of dopamine is evenly distributed on the graphite surface, because the lithium lanthanum zirconium oxygen solid electrolyte is segregated on the graphite surface.
[0069] Comparative Example 3
[0070] Using excess dopamine coated 5% lithium lanthanum zirconium oxygen solid electrolyte
[0071] (1) Dissolve 0.5 g of dopamine hydrochloride in a mixed solution of water and ethanol in a volume ratio of 1:1, then add 5 g of natural graphite and stir evenly.
[0072] (2) NH3·H2O was added dropwise to the above solution to adjust the solution to a pH of 8.3, and the mixed solution was magnetically stirred at 200 rpm for 24 h to polymerize dopamine. The reaction solution was filtered, and deionized water and anhydrous ethanol were alternately filtered and washed until neutral. The powder was collected and placed in an oven at 70°C for 10 h under vacuum to obtain dopamine-coated graphite.
[0073] (3) The dopamine-coated graphite is dispersed in deionized water, and lithium nitrate, lanthanum nitrate hexahydrate, and zirconium oxychloride octahydrate are added to the water in a stoichiometric ratio, with the corresponding mass of lithium lanthanum zirconium oxygen being 5% of the added natural graphite. Then, an additional 10% of lithium nitrate is added, and then citric acid monohydrate is added in a molar amount of 2 times the cationic amount.
[0074] (4) The mixed solution was magnetically stirred at 80°C at 300 rpm until the solution was evaporated to dryness, and then the evaporated material was placed in an oven at 80°C for vacuum drying for 10 h.
[0075] (5) The dried mixed material is transferred to a tubular furnace, and heated to 900° C. at a heating rate of 5° C. / min under argon gas protection for heat treatment for 7 h to obtain lithium lanthanum zirconium oxygen solid electrolyte coated graphite.
[0076] The electrochemical performance test results of the final product are as follows Fig.11 As shown, the results show that the capacity of the final product decays rapidly at a current density of 1C and cannot work normally.
[0077] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite, characterized in that: The method steps include: (1) dissolving dopamine hydrochloride in a mixed solution of water and ethanol, and then adding natural graphite and stirring to disperse uniformly to obtain a dispersion; (2) adjusting the dispersion to be weakly alkaline, stirring to polymerize and adsorb dopamine on the surface of natural graphite, filtering, collecting powder and vacuum drying to obtain dopamine-coated graphite; (3) dispersing the dopamine-coated graphite in deionized water, adding lithium nitrate, lanthanum nitrate hexahydrate and zirconium oxychloride octahydrate, and then adding citric acid monohydrate to obtain a mixed reaction system; (4) heating and stirring until the solution in the mixed reaction system is evaporated to dryness, and vacuum drying the evaporated material to obtain a precursor material; (5) The precursor material is transferred to a tubular furnace and subjected to heat treatment under a protective gas atmosphere to obtain a lithium ion battery negative electrode material having a lithium lanthanum zirconium oxide solid electrolyte coated with graphite.
2. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (1), the mass ratio of dopamine hydrochloride to natural graphite is 0.02-0.04:1; preferably, in step (1), the volume ratio of water to ethanol is 1:1-1.
5.
3. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (2), NH3·H2O is added dropwise to adjust the pH value of the dispersion to 8.3-8.5; preferably, in step (2), the stirring rate is 200-300 rpm and the time is 24-32 h.
4. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (2), deionized water and anhydrous ethanol are used alternately for filtration and washing until neutrality occurs; preferably, in step (2), the vacuum drying temperature is 60 to 80° C. and the time is 6 to 10 hours.
5. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (3), lithium nitrate, lanthanum nitrate hexahydrate, and zirconium oxychloride octahydrate are added according to the chemical dosage ratio of lithium lanthanum zirconium oxygen, and an additional 10% to 12% excess lithium nitrate is added, and the corresponding mass of lithium lanthanum zirconium oxygen is 3% to 10% of the mass of natural graphite.
6. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (3), the molar amount of citric acid monohydrate is 1.5 to 2 times that of the cation in the mixed reaction system.
7. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (4), the heating and stirring temperature is 70-90° C., and the stirring rate is 200-300 rpm; preferably, in step (4), the vacuum drying temperature is 60-80° C., and the time is 6-10 h.
8. The method for preparing a negative electrode material for a lithium ion battery of a lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as claimed in claim 1, characterized in that: In step (5), the protective gas is nitrogen or an inert gas; preferably, in step (5), the heat treatment temperature is 850-950°C, the treatment time is 5-7h, and the heating rate is 5-10°C / min.
9. A lithium ion battery negative electrode material of lithium lanthanum zirconium oxygen solid electrolyte coated with graphite, characterized in that: The material is prepared by the method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The negative electrode material of the battery is a lithium-ion battery negative electrode material of lithium lanthanum zirconium oxygen solid electrolyte coated with graphite as described in claim 9.
Citation Information
Patent Citations
All-solid-state lithium-sulfur battery composite positive electrode material and preparation method thereof
CN112599759A
Composite solid electrolyte and preparation method thereof
CN113054238A
Preparation method of boron-doped lithium lanthanum zirconate coated graphite composite material
CN113889594A
Solid electrolyte and preparation method thereof, positive electrode material, positive electrode plate and solid-state battery
CN116646590A
Organic-inorganic composite solid electrolyte material and organic-inorganic composite solid electrolyte membrane using same
CN117254095A